PROMOSI KESEHATAN KESELAMATAN DAN KESEHATAN KERJA (K3) SEKOLAH DI SMA SANTO YOSEF DURI - Ignatius Yulianto Wibowo (Jurnal Abdimas Bina Bangsa, 2022)
During school activities, students, teachers, and staffs are potentially exposed to hazards. Therefore, occupational safety and health (OSH) at schools is important to understand by those involved in activities at schools. In regards to accidents and diseases prevention due to school activities, health promotion is conducted to gain better understanding of OSH. In fact, Greater awareness of OSH results in more positive attitude towards OSH, which eventually leads to changes in life practice. OSH promotion was held on 4 April 2022 at SMA Santo Yosef Duri. The community service began with presentation and interactive dialogue.  The participants responded positively to this event. The discussion and interactive dialogue brought about action plan: 1) identification of potential hazards and 2) Attempts to prevent accidents and diseases due to school activities. Finally, Evaluation of preventive measures which have been designed will be performed periodically